Upaya Peningkatan Hasil Belajar Melalui Model Pembelajaran Problem Based Learning Untuk Materi Penyajian Data Pada Siswa Kelas VII SMP SATAP Ngaluroga - Vivien Restianim; gregorius weu (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
The problem that occurred in Alvares Paga Junior High School which was appointed by researchers was the low student learning outcomes for tata presentation material. This research aims to to find out the increase in activity and student learning outcomes for data presentation material through the Problem Based Learning learning model in class VII students of SMP SATAP Ngaluroga. The research setting uses classroom action research conducted in two cycles, each consisting of of planning, implementation, observation and reflection. The location of this study was conducted at SMP SATAP Ngaluroga. The subjects were class VII students, totaling 32 people. The results of the study shows that (1) the students learning activities were obtained by 56% and cycle 2 by 84% with an increase of 28% so that it was said to be good while (2) the students learning outcomes in cycle I obtained an average value of 57.34 with a percentage mastery learning classical is 53.125%, and in cycle II the average value is 90.312 with a percentage of classical learning completeness of 100% with an increase of 46.875%. The conclusion of this study is that the learning outcomes of class VII students have increased using the Problem Based learning model.